Evaluation of activity of peroxidases contained in various plant sources - Solovyeva, Anna A.; Lebedeva, Olga E.; Thi Pham, Trinh (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2023)
In this study, the decolorization reaction of aqueous solution bromophenol blue dye was carried out in the presence of hydrogen peroxide and peroxidase contained in the roots of horseradish (Armoracia rusticana), radish (Raphanus sativus var. radicula), yellow turnip (Brassica napobrassica), daikon (Raphanus sativus), black radish (Raphanus sativus ‘Niger’), green radish (Raphanus) or stalk of white cabbage (Brassica capitata). The reaction was carried out at an initial dye content of 25,1 μM, a hydrogen peroxide concentration of 0,4 mM, at t = 24 °C and pH 4,01, the peel of various vegetables was used as a source of peroxidase; it was inserted into the reaction without enzyme primary extraction. When using horseradish waste, black radish, white cabbage, turnips, it is possible to get the degree of decolorization of the dye in its aqueous solution by 95%. The maximum rate and Michaelis constants of the enzymatic reaction are calculated by the linearization method in the Linuiver – Burke coordinates. It is shown that the activity of peroxidase contained in the peel of black radish persists with an increase in temperature from 23 to 40 °С.